Fomration of hydroxylated polychlorinated diphenyl ethers mediated by Structural Fe(III) in smectites. (July 2019) - Wang, Yi; Liu, Cun; Peng, Anping; Gu, Cheng
Abstract: Fe(III)-bearing clay minerals are ubiquitous in the environment. However, the fate of organic contaminants mediated by structural Fe(III) in clays was rarely reported. Here we demonstrated that hydroxylated polychlorinated diphenyl ethers (HO-PCDEs) could be spontaneously formed from the reaction of 2, 4, 6-trichlorophenol (2, 4, 6-TCP) with three native smectites: SWy-2, NAu-1, and NAu-2. Further research demonstrated that the structural Fe(III) in smectite is indispensable for the mediation of 2, 4, 6-TCP to produce chlorophenoxy radical for the subsequent dimerization. The reaction is highly dependent on the relative humidity of the system and the site occupancy of structural Fe(III). Active structural Fe(III) in NAu-2 that played a significant role in the dimerization reaction is relatively more distorted, which would interact strongly with 2, 4, 6-TCP under low humidity and be inhibited by water molecules. Hence reaction on NAu-2 is suppressed as relative humidity increases. Whereas, water molecules would reduce the activation and reaction energies via forming a hydrogen bond with reaction intermediates, thus enhancing the reactions on SWy-2 and NAu-1 with less water sensitive structural Fe(III). Considering the wide distribution of Fe(III)-bearing smectites in the environment, the contribution of structural Fe(III) for the formation of more toxic dioxin-like compounds from chlorophenols might need to be taken into consideration to evaluate their potential environmental risks. Graphical abstract: Image 1 Highlights: Native SWy-2, NAu-1 and NAu-2 could mediate 2, 4, 6-trichlorophenol to produce HO-PCDEs. Structural Fe(III) in the smectites is indispensable for the reaction. The reaction is highly dependent on relative humidity and structural Fe(III) site occupancy. Compared with SWy-2 and NAu-1, relative humidity has a totally opposite effect on the reaction of NAu-2.